Be Aware of Transient Dissolution Processes in Co3O4 Acidic Oxygen Evolution Reaction Electrocatalysts - Priamushko, Tatiana; Franz, Evanie; Logar, Anja; Bijelić, Lazar; Guggenberger, Patrick; Escalera-López, Daniel; Zlatar, Matej; Libuda, Jörg; Kleitz, Freddy; Hodnik, Nejc; Brummel, Olaf; Cherevko, Serhiy (Journal of the American Chemical Society, 2025)
Recently, cobalt-based oxides have received considerable attention as an alternative to expensive and scarce iridium for catalyzing the oxygen evolution reaction (OER) under acidic conditions. Although the reported materials demonstrate promising durability, they are not entirely intact, calling for fundamental research efforts to understand the processes governing the degradation of such catalysts. To this end, this work studies the dissolution mechanism of a model Co3O4 porous catalyst under different electrochemical conditions using online inductively coupled plasma mass spectrometry (online ICP-MS), identical location scanning transmission electron microscopy (IL-STEM), and differential electrochemical mass spectrometry (DEMS). Despite the high thermodynamics tendency reflected in the Pourbaix diagram, it is shown that the cobalt dissolution kinetics is sluggish and can be lowered further by modifying the electrochemical protocol. For the latter, identified in this study, several (electro)chemical reaction pathways that lead to the dissolution of Co3O4 must be considered. Hence, this work uncovers the transient character of cobalt dissolution and provides valuable insights that can help to understand the promising stability of cobalt-based materials in already published works and facilitate the knowledge-driven design of novel, stable, abundant catalysts toward the OER in an acidic environment.
CRIS-Team Scopus Importer:2025-01-31